Role of Mathematical Communication for Learning Mathematics - Khadka, Jaya Bahadur (Journal of Educational Research and Innovation, 2024)
Mathematical communication is increasingly recognized as a crucial component of effective mathematics learning. This research paper examines the role of mathematical communication in enhancing students' understanding and proficiency in mathematics. The objectives of the study are to explore how communication supports learning in mathematics, identify strategies that teachers can employ to improve students' mathematical communication skills, and assess the impact of these skills on overall student achievement. The research employs a mixed-methods approach, combining quantitative and qualitative data from surveys, classroom observations, and interviews with mathematics teachers and students. A sample of 50 secondary school students and 2 mathematics teachers were selected from various schools. Quantitative data were gathered through surveys assessing students' communication skills and mathematics achievement, while qualitative data were obtained through observations of classroom interactions and interviews with teachers regarding their instructional practices. The findings reveal that students with stronger mathematical communication skills demonstrated a higher level of understanding and problem-solving ability. Teachers who actively promoted mathematical communication through structured tasks, classroom discussions, and opportunities for students to explain their reasoning reported improved student engagement and learning outcomes. Furthermore, the study found that mathematical communication not only facilitated individual learning but also encouraged collaborative problem-solving and peer learning. In conclusion, the study highlights the significant role of mathematical communication in fostering deeper understanding and improving mathematical proficiency. Effective communication allows students to articulate their thinking, engage with mathematical concepts more critically, and collaborate with others. The study recommends that teachers incorporate mathematical communication as a central element of their instructional practices to enhance student learning and success in mathematics.